Innovative Strategy for Sundanese Dance Learning Based on Experiential Learning in Outcome-Based Education Curriculum to Achieve Quality Education - Arsih, Utami; Lanjari, Restu; Hutagalung, Fonny Dameaty (Universitas Negeri Semarang, 2025)
This study aims to develop a Sundanese dance learning model based on Experiential Learning in the Outcome-Based Education curriculum, to enhance the quality of arts education. The urgency of this study stems from the limited exploration of the integration between Outcome-Based Education, Experiential Learning, and cultural preservation in Sundanese dance learning, despite its importance in achieving quality education goals in accordance with Sustainable Development Goal. The method employed is a mixed approach (qualitative and quantitative), utilizing data collection techniques that include interviews, observations, and surveys of students, lecturers, and dance teachers. The results indicate that the application of this model can enhance student engagement, creativity, and cultural understanding, with a statistically significant average increase of 35.35%. This model also strengthens the preservation of Sundanese cultural values through direct learning experiences. Research recommendations include the adoption of similar models in other art study programs, the development of a more responsive curriculum, and the use of digital technology to support innovative and sustainable learning.